Housing preferences and access to public rental housing among migrants in Chongqing, China. (September 2018) - Zhou, Jing; Musterd, Sako
Abstract: Since 2010, a fundamental transition in the Chinese housing system has been the policy of opening access to public rental housing (PRH) for Chinese (intra-national) migrants. While migrants are increasingly stating that they have a preference for public rental housing, some of them did not act upon such a desire while others have been insistent on it. Responding to a lack of understanding of the relationship between migrants and the public rental housing regime, the study examines three stages of migrants' access to public rental housing with a focus on exploring individual and housing differences between migrants. The three stages comprise (1) migrants who stated a preference for PRH; (2) migrants who translated the stated preference into action; and (3) migrants who persisted in the PRH application, those who applied four times or more, and those who gave up applying for a PRH after having applied one-to-three times. The study combines survey and statistical data from Chongqing, the first city to extensively offer migrants equal access to public rental housing on a broad scale. Results reveal that migrants with inter-provincial hukou, lower income, larger family size, more urban relatives and an expectation to improve their housing conditions were more likely to state a preference for PRH and to eventually realize such a preference. However, although migrants with unstable occupations also stated a preference for PRH, the application criteria restricted them from continually trying to realize their preferences. Moreover, migrants were less likely to move from employer supplied housing to PRH compared with moving from private rental housing to PRH. The consistent application for PRH was more likely to relate to the desire for single family housing, centrally located and larger housing, while these preferences and the PRH provision did not match.